2013
DOI: 10.1159/000356796
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in Acute Stroke Patients with Cerebral Small Vessel Disease

Abstract: Background: Thrombolytic treatment is of proven benefit in acute ischemic stroke. The term cerebral small vessel disease (SVD) refers to a group of pathological processes affecting the small arteries, arterioles, venules and capillaries of the brain, and encompasses both ischemic and hemorrhagic lesions. Lacunar stroke, an expression of SVD, is associated with an unfavorable long-term prognosis for an increased risk of death, recurrent stroke and cognitive dysfunction. Nonetheless, the efficacy and safety of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 40 publications
(60 reference statements)
1
57
1
1
Order By: Relevance
“…Three studies reported worse outcomes in ischemic stroke patients with WMLs after IVT in 400, 14 200, 13 164 patients. 12 However, in 1 study of 800 IVT-treated patients, severe van Swieten scores 3,4 were only associated with poor outcome (mRS, 2-6) or death in univariate, but not after adjusted analyses, whereas there remained a significant association after adjustments in the present study. 15 This difference is probably because of sample size because the cutoff values for severe WMLs on van Swieten scale covered only 71 (8.6%) patients in the cited study, whereas there were 481 (18.8%) patients with severe WMLs in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…Three studies reported worse outcomes in ischemic stroke patients with WMLs after IVT in 400, 14 200, 13 164 patients. 12 However, in 1 study of 800 IVT-treated patients, severe van Swieten scores 3,4 were only associated with poor outcome (mRS, 2-6) or death in univariate, but not after adjusted analyses, whereas there remained a significant association after adjustments in the present study. 15 This difference is probably because of sample size because the cutoff values for severe WMLs on van Swieten scale covered only 71 (8.6%) patients in the cited study, whereas there were 481 (18.8%) patients with severe WMLs in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…Our department's guidelines from the beginning of thrombolysis treatment have stated severe microangiopathy to be a relative contraindication for thrombolysis, although there is no evidence for WMLs being a contraindication for IVT, and this is not mentioned in the guidelines for the early management of patients with acute ischemic stroke. 1,6,8 For clinical use in CT-imaged patients with acute stroke our study supports the use of the Wahlund score with a cutoff of more than focal lesions at any frontal or parieto-occipital site (Wahlund any site score, >1).…”
Section: Curtze Et Al White Matter Lesions and Thrombolysis 2153supporting
confidence: 73%
“…5 Because of increased bleeding risk, WMLs are considered a relative, but not an absolute, contraindication for thrombolysis. 6,7 Yet, the attributable risk of WMLs to the risk of sICH in ischemic stroke patients treated with IVT in the general population is uncertain, 6 and major guidelines for treating acute ischemic stroke lack a statement on WMLs about IVT. 1,8 Considering the modest patient numbers and conflicting results in previous studies, we aimed to investigate the risk for sICH in the presence of WMLs in a large single-center cohort of ischemic stroke patients treated with IVT.…”
mentioning
confidence: 99%
“…Thus, the presence of small vessel disease causes a poor prognosis by causing both increased bleeding risk and decreased recovery. Nevertheless, the results of IV tPA in such patients are still better and IV tPA should be administered (50).…”
Section: Question: Can IV Tpa Be Administered To Patients With Cerebrmentioning
confidence: 99%